2009
DOI: 10.1088/0004-637x/707/1/370
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Ultrahigh Energy Nuclei in Clusters of Galaxies: Resulting Composition and Secondary Emissions

Abstract: We study the survival of ultrahigh energy nuclei injected in clusters of galaxies, as well as their secondary neutrino and photon emissions, using a complete numerical propagation method and a realistic modeling of the magnetic, baryonic and photonic backgrounds. It is found that the survival of heavy nuclei highly depends on the injection position and on the profile of the magnetic field. Taking into account the limited lifetime of the central source could also lead in some cases to the detection of a cosmic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
133
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 114 publications
(143 reference statements)
11
133
1
Order By: Relevance
“…[4][5][6][7][8]). Various theoretical interpretations include possibilities of hadronic (pp) production in cosmic-ray (CR) reservoirs [9] and photohadronic (pγ) production in hidden CR accelerators [10][11][12][13][14], and the observed neutrino intensity at ∼0.1-1 PeV energies is consistent with earlier models [15][16][17][18]. Only a fraction of the observed events could have Galactic origins (e.g., Refs.…”
supporting
confidence: 57%
“…[4][5][6][7][8]). Various theoretical interpretations include possibilities of hadronic (pp) production in cosmic-ray (CR) reservoirs [9] and photohadronic (pγ) production in hidden CR accelerators [10][11][12][13][14], and the observed neutrino intensity at ∼0.1-1 PeV energies is consistent with earlier models [15][16][17][18]. Only a fraction of the observed events could have Galactic origins (e.g., Refs.…”
supporting
confidence: 57%
“…With the very flat magnetic field radial profile in the intra-cluster medium predicted by the cosmological simulations of [146], the authors found that particles with rigidity below ∼ 10 19 V were strongly confined and as a result very strong mangnetic horizon effects were expected in the propagated spectrum (depleted below 10 19 eV) and the composition (the intermediate and heavy nuclei being strongly suppressed at all energies). More recently, the escape of UHECRs from galaxy cluster environments was considered in [152]. This study was based on the output of the structure formation simulations by [149] and considered, besides the effect of the intra-cluster magnetic fields (whose radial attenuation was much steeper than in [146]), the enhancement of the photon background due to the contribution of galaxies inside the cluster and the contribution of hadronic interactions.…”
Section: Cosmic Magnetic Fieldsmentioning
confidence: 99%
“…We compute the gamma-ray signal with numerical Monte Carlo simulations, using the code presented in Kotera et al (2009). In a first step, we propagate ultrahigh energy cosmic-rays (protons and heavier nuclei) in one of the three-dimensional magnetic field models described above.…”
Section: Numerical Codementioning
confidence: 99%